2011
DOI: 10.1039/c1ra00393c
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry of graphene: not such a beneficial electrode material?

Abstract: We critically evaluate the reported electro-catalysis of graphene using inner-sphere and outer-sphere electrochemical redox probes, namely potassium ferrocyanide (II) and hexaammine-ruthenium(III) chloride, in addition to L-ascorbic acid and b-nicotinamide adenine dinucleotide. Well characterised commercially available graphene is utilised which has not been chemically treated, is free from surfactants, and as a result of its fabrication has an extremely low oxygen content allowing the electronic properties to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
264
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 222 publications
(288 citation statements)
references
References 51 publications
18
264
2
Order By: Relevance
“…A combination of CNT and graphene may be an effective way to solve this problem [137,138]. Dai's group has demonstrated that CNT-graphene complexes can exhibit excellent activity and stability towards ORR in both acidic and basic electrolytes [139].…”
Section: The Composites Of Ncnts and Ng For Orrmentioning
confidence: 99%
“…A combination of CNT and graphene may be an effective way to solve this problem [137,138]. Dai's group has demonstrated that CNT-graphene complexes can exhibit excellent activity and stability towards ORR in both acidic and basic electrolytes [139].…”
Section: The Composites Of Ncnts and Ng For Orrmentioning
confidence: 99%
“…[6][7][8] Various types of graphene based sensors have been developed in the recent past, and role of edge and basal planes of graphene in determining the effective sensitivity have also been studied. 9 However, in a recent report, it was established that apart from the effects of basal and edge planes of graphene in net electron transfer process, its atomic thickness and structure are insignicant in electron transfer process, and the electrochemical response will not vary much from single to few layers of graphene.…”
Section: Introductionmentioning
confidence: 99%
“…This method of preparation requires considerable skill and experience, which could be the main reason why very few research groups reported on electrochemistry of ME graphene flakes [2][3][4][5]. As a consequence, chemical vapour deposition (CVD) graphene, as well as fewlayer graphene sheets prepared via liquid-phase exfoliation or reduction of graphene oxide, are often substituted for ME graphene for simplicity and scalability [6][7][8][9]. However, these alternatives often yield graphene prepared in an uncontrolled and illdefined manner, which is reflected by inconsistencies between the conclusions drawn about the electrochemistry of graphene [2,3,7,8,10,11].…”
Section: Introductionmentioning
confidence: 99%